Immunological Effects of Histotripsy for Cancer Therapy - Hendricks-Wenger, Alissa; Hutchison, Ruby; Vlaisavljevich, Eli; Allen, Irving Coy (Frontiers in Oncology, 2021)
Cancer is the second leading cause of death worldwide despite major advancements in diagnosis and therapy over the past century. One of the most debilitating aspects of cancer is the burden brought on by metastatic disease. Therefore, an ideal treatment protocol would address not only debulking larger primary tumors but also circulating tumor cells and distant metastases. To address this need, the use of immune modulating therapies has become a pillar in the oncology armamentarium. A therapeutic option that has recently emerged is the use of focal ablation therapies that can destroy a tumor through various physical or mechanical mechanisms and release a cellular lysate with the potential to stimulate an immune response. Histotripsy is a non-invasive, non-ionizing, non-thermal, ultrasound guided ablation technology that has shown promise over the past decade as a debulking therapy. As histotripsy therapies have developed, the full picture of the accompanying immune response has revealed a wide range of immunogenic mechanisms that include DAMP and anti-tumor mediator release, changes in local cellular immune populations, development of a systemic immune response, and therapeutic synergism with the inclusion of checkpoint inhibitor therapies. These studies also suggest that there is an immune effect from histotripsy therapies across multiple murine tumor types that may be reproducible. Overall, the effects of histotripsy on tumors show a positive effect on immunomodulation.